Ipomoea pes-caprae Beach Morning Glory - Edward Gilman (EDIS)
This document provides a detailed overview of the beach morning glory (Ipomoea pes-caprae), an herbaceous vine native to Florida and coastal regions from Texas to Georgia. It describes the plant’s physical characteristics, including its height, leaf shape, and flower color, as well as its growth habits and environmental tolerances. The beach morning glory is noted for its rapid growth, high drought and salt tolerance, and usefulness as a ground cover and sand binder on coastal dunes. The document also highlights the plant’s invasive potential and suitability for specific planting zones. Original publication date October 1999.